Prognostic Significance of Tumor-Associated Macrophages in Chondroblastoma and Their Association with Response to Adjuvant Radiotherapy - Zheng BW (Dove Medical Press, 2021)
Bo-Wen Zheng,1,2 Min-Liang Yang,2 Wei Huang,3 Bo-Yv Zheng,4 Tao-Lan Zhang,5 Jing Li,2 Guo-Hua Lv,2 Yi-Guo Yan,1,* Ming-Xiang Zou1,* 1Department of Spine Surgery, The First Affiliated Hospital, University of South China, Hengyang, 421001, People’s Republic of China; 2Department of Spine Surgery, The Second Xiangya Hospital, Central South University, Changsha, 410011, People’s Republic of China; 3Health and Management Centre, The First Affiliated Hospital, University of South China, Hengyang, 421001, People’s Republic of China; 4Department of Orthopedics Surgery, General Hospital of the Central Theater Command, Wuhan, 430061, People’s Republic of China; 5Department of Radiation Oncology, Indiana University School of Medicine, IU Simon Comprehensive Cancer Center, Indianapolis, IN, 46202, USA*These authors contributed equally to this workCorrespondence: Ming-Xiang ZouDepartment of Spine Surgery, The First Affiliated Hospital, University of South China, 69 Chuanshan Road, Hengyang, Hunan, 421001, People’s Republic of ChinaTel +86 73485295624Fax +86 73482654334Email zouwei8887@126.comYi-Guo YanDepartment of Spine Surgery, The First Affiliated Hospital, University of South China, 69 Chuanshan Road, Hengyang, Hunan, 421001, People’s Republic of China, +86 73485295624, +86 73482654334Email yan_yiguo@qq.comObjective: Chondroblastoma (CB) is a rare and locally growing cartilage-derived tumor. Currently, clinical implications of tumor-associated macrophages (TAMs) in CB remain unclear. In this study, we sought to analyze the relationship between TAM parameters (including densities of CD68+ and CD163+ cells as well as the CD163+/CD68+ ratio) and clinicopathological characteristics and survival of patients.Methods: Immunohistochemistry was used to assess TAM subtypes for CD68 and CD163, as well as the expression levels of p53, CD34, and Ki-67 on tumor cells in 132 tissue specimens retrieved between July 2002 and April 2020. Then, TAM parameters were retrospectively analyzed for their associations with patient outcomes (local recurrence-free survival [LRFS] and overall survival [OS]) and clinicopathological features.Results: TAM densities were significantly higher in axial chondroblastoma tissue than in extra-axial chondroblastoma tissue. Moreover, the number of CD163+ TAMs was positively correlated with tumor invasion of surrounding tissues and high expression of CD34 and Ki-67 on tumor cells, whereas CD163+ cell density and the CD163/CD68 ratio were negatively associated with patient response to adjuvant radiotherapy. Univariate Kaplan–Meier analysis revealed that the number of CD68+ and CD163+ lymphocytes was significantly associated with both LRFS and OS. Multivariate Cox regression analysis showed that CD163+ and CD68+ cell levels were independent prognostic factors of LRFS, while TAM data independently predicted OS. More importantly, in subgroup analysis based on three significant factors in univariate survival analysis (including tumor location, adjuvant radiotherapy, and surrounding tissue invasion by tumors), the TAM parameters still displayed good prognostic performance.Conclusion: These data suggest that TAM may significantly affect the biological behavior of CB. We hypothesize that modulating the TAM level or polarization status in the microenvironment may be an effective approach for CB treatment.Keywords: chondroblastoma, tumor-associated macrophages, tumor immune microenvironment, prognostic factors, survival analysis